AfriKaleidoskop meets ARTE: Afrikas vergessene Geschichte – Wer war Jan Conny?: Diskussion - Mark-Thiesen, Cassandra (Afrikaleidoskop meets ARTE, 2026)
This video documents the public discussion following an ARTE screening hosted by the Africa Multiple Cluster of Excellence at the Kulturhaus Neuneinhalb (Bayreuth) on April 15, 2026. The event featured Episode 1 of the ARTE documentary series “Afrikas vergessene Geschichte - Wer war Jan Conny” (Africa’s Forgotten History), presented as part of the “AfriKaleidoskop meets ARTE” screening series. Following the screening, the discussion brought together filmmaker Ntivyihabwa Jean-Alexander and historian Dr. Cassandra Mark-Thiesen, offering insights into the film’s themes and their broader historical and societal contexts. The conversation engages with questions of history, memory, and representation, continuing the dialogue initiated by the film within an interdisciplinary and public setting. 👉 Note: The discussion is held in German.